One Day in Denmark: Comparison of Phenotypic and Genotypic Antimicrobial Susceptibility Testing in Bacterial Isolates From Clinical Settings - Rebelo, Ana Rita; Bortolaia, Valeria; Leekitcharoenphon, Pimlapas; Hansen, Dennis Schrøder; Nielsen, Hans Linde; Ellermann-Eriksen, Svend; Kemp, Michael; Røder, Bent Løwe; Frimodt-Møller, Niels; Søndergaard, Turid Snekloth; Coia, John Eugenio; Østergaard, Claus; et al. (Frontiers in Microbiology, 2022)
Antimicrobial susceptibility testing (AST) should be fast and accurate, leading to proper interventions and therapeutic success. Clinical microbiology laboratories rely on phenotypic methods, but the continuous improvement and decrease in cost of whole-genome sequencing (WGS) technologies make them an attractive alternative. Studies evaluating the performance of WGS-based prediction of antimicrobial resistance (AMR) for selected bacterial species have shown promising results. There are, however, significant gaps in literature evaluating the applicability of WGS as a diagnostic method in real-life clinical settings against the range of bacterial pathogens experienced there. Thus, we compared standard phenotypic AST results with WGS-based predictions of AMR profiles in bacterial isolates without pre-selection of defined species, to evaluate the applicability of WGS as a diagnostics method in clinical settings. We collected all bacterial isolates processed by all Danish Clinical Microbiology Laboratories in one day. We randomly selected 500 isolates without any pre-selection of species. We performed AST through standard broth microdilution (BMD) for 488 isolates (n=6,487 phenotypic AST results) and compared results with in silico antibiograms obtained through WGS (Illumina NextSeq) followed by bioinformatics analyses with ResFinder 4.0 (n=5,229 comparisons). A higher proportion of AMR was observed for Gram-negative bacteria (10.9%) than for Gram-positive bacteria (6.1%). Comparison of BMD with WGS data yielded a concordance of 91.7%, with discordant results mainly due to phenotypically susceptible isolates harbouring genetic AMR determinants. These cases corresponded to 6.2% of all isolate-antimicrobial combinations analysed, and to 6.8% of all phenotypically susceptible combinations. We detected fewer cases of phenotypically resistant isolates without any know genetic resistance mechanism, particularly 2.1% of all combinations analysed, which corresponded to 26.4% of all detected phenotypic resistances. Most discordances were observed for specific combinations of species-antimicrobial: macrolides and tetracycline in streptococci, ciprofloxacin and β-lactams in combination with β-lactamase inhibitors in Enterobacterales, and most antimicrobials in Pseudomonas aeruginosa. WGS has the potential to be used for surveillance and routine clinical microbiology. However, in clinical microbiology settings and especially for certain species and antimicrobial agent combinations, further developments in AMR genes databases are needed to ensure higher concordance between in silico predictions and expected phenotypic AMR profiles.